Voters' confidence and good governance in Nigeria: a comparative analysis of 2015 and 2019 presidential elections / Abdulrazaq Idowu Amao, Abdulrauf Ambali and Akeem Araba - Amao, Abdulrazaq Idowu; Ambali, Abdulrauf; Araba, Akeem (Universiti Teknologi MARA, 2022)
Nigeria has undergone the two faces of electoral integrity: the good and the bad. For the avoidance of doubt, Nigerian elections between 1999 and 2007 were generally rated to be lacking in integrity. This may have accounted for the low quality of governance in Nigeria during those periods. It is against this background that this study set out to examine the relationship between voters' confidence and good governance in Nigeria. The study used (mixed method) both primary and secondary sources of data collection. For the primary source of data a well-structured questionnaire and closed ended interview were conducted. A total of 1200 questionnaires were administered in three states (Kwara, Ekiti and Rivers) in three different geo-political zones in Nigeria. And a total of forty-five interviewees/people were interviewed in the three states. On a face to face and well structure interview. Both qualitative and quantitative method of data analysis was used. The study uses Principal Agency theory. The study finds out that there is significant contribution of Voters' Confidence to Good governance in Nigeria. The study concluded that there is a significant contribution of Voters' Confidence in the achievement of Good governance in Nigeria. And the study have also made it clear that for any nation to achieve good governance, it has to improve the Voters' Confidence in the electoral process of the country.